DETECTION OF ANTIBIOTIC RESISTANT IN Escherichia coli FROM THE REPRODUCTIVE TRACT OF BALI CATTLE ON SMALLHOLDER FARM - Kholik Kholik (Jurnal Biosains Pascasarjana, 2022)
Escherichia coli originating from animals, humans, and the environment can spread antibiotic-resistant genes and can encourage antimicrobial resistance (AMR) which is a global health problem. The purpose of this study was to detect the presence of Escherichia coli which is resistant to several antibiotics from the reproductive tract of Bali cattle on smallholder farms on the island of Lombok. This research is a cross-sectional study conducted from March to June 2021 using 8 female Bali cattle that experience reproductive disorders on community farms in Lando Village, East Lombok Regency to collect their reproductive tract fluids using an artificial insemination plastic sheet gun. Reproductive fluid samples are placed on BHIB (Brain Heart Infusion Broth) medium. Escherichia coli cultures were carried out on Eosin Methylene Blue Agar (EMBA) and identified by Gram staining and biochemical tests conducted at the Public Health and Calibration Laboratory, West Nusa Tenggara Province. Antibiotic sensitivity test on isolated Escherichia coli was carried out by disc diffusion method using 5 antibiotics including Penicillin G 10U, Oxytetracycline 30 µg, Gentamicin 10 µg, Tetracycline 30 µg, and Cefotaxime 30 µg. The results showed that 2 (two) 25% Escherichia coli bacteria were successfully cultured on EMBA media and isolated from 8 samples of the reproductive fluids of Bali cattle that were collected. The results of the Escherichia coli sensitivity test to antibiotics found that Escherichia coli samples were 100% resistant to Penicillin G, 100% resistant to Oxytetracycline, 100% resistant to Gentamicin, and 50% resistant to Tetracycline, and 100% resistant to Cefotaxime from 2 isolated Escherichia coli. This explains that Bali cattle in community farms have the potential to spread Escherichia coli which has an impact on the emergence of AMR.